A set of online tools for teaching chemistry considering a systematic approach to the educational process - Manapova, Saltanat; Shaikhova, Bakhyt; Kumarbekuly, Sanat; Mikushina, Irina; Afanasenkova, Irina (International Journal of Innovative Research and Scientific Studies, 2025)
This article discusses the development and application of a set of online tools for teaching chemistry via a systems approach. The possibilities of integrating tools such as virtual laboratories, interactive simulators, and knowledge control platforms into the educational process are analyzed. These tools not only enhance the learning experience but also foster a deeper understanding of complex chemical concepts. The key advantages of the systems approach are highlighted, including personalization of learning, development of critical thinking, and improvement of practical skills. The use of digital tools allows students to experiment virtually, bridging the gap between theory and practice. The challenges associated with the implementation of online education, such as the need for teacher training and access to quality resources, are also considered. These challenges can be addressed through professional development programs and ensuring equitable access to technology. A model for assessing the effectiveness of using digital tools based on the level of teacher qualifications, digital equipment, and the size of groups is presented. In conclusion, there is a need to adapt curricula that incorporate modern technologies to improve the quality of chemistry teaching, ensuring that both educators and students benefit from these advancements.